(untitled) (Bangladesh Journal of Medical Science, 2023)
objective: Iron is the most abundant metal within the mitochondrial matrix . Ferritin reflects bodyironstores. This study aimed to assess the association between serum ferritin levels and mitochondrial function in children. Methods: Two hundred and forty-three children from four governmental primary schools in Mosul city in Iraq were randomly selected by a multistage random sampling method. Their age range was 6-12 years. Mitochondrial function tests involved measurement of serum lactate, serum pyruvate, and L-Carnitine were analyzed in all selected children along with serum ferritin. Results: Lower levels of serum ferritin weresignificantly associated with higher levels of serum lactate, serum lactate/serum pyruvate ratio. There was a significant negative correlation (p = 0.000, - 0.296,- 0.286) between mean serum ferritin level and mean serum lactate, serum lactate / serum pyruvate ratio respectively.There were significant differences (p= 0.000) in mean serum level of mitochondrial function tests (Lactate, L- Carnation, and L/P ratio) in comparing children possessing a normal level of serum ferritin versus those with a low serum ferritin level of < 12 ng/ml. ROC analysis showed that when the area under the curve (AUC) was 0.761 ± SE 0.37, a cut off value 4.79 ng/ml of serum ferritin was significantly (p=0 .000) associated with sensitivity of 100 % and 1- specificity of 0.861 value with presence of L: P molar ratio of ≤ equal 20. Conclusion:Serum ferritin < 12 ng/ ml represntsmitochondrial deficient level. Serum ferritin < 4.79 ng/ml was the critical value at which only 8.6% of children will have a healthy mitochondrial function. Bangladesh Journal of Medical Science Vol. 22 No. 02 April’23 Page : 374-378